Mother-to-Child transmission of HCV among HIV/HCV Co-infected women - Checa Cabot, Claudia A. (2013)
BACKGROUND: Maternal human immunodeficiency virus (HIV) coinfection has been associated with increased hepatitis C virus (HCV) mother-to-child transmission (MTCT). We hypothesized that HCV/HIV-coinfected women with well-controlled HIV disease would not have increased HCV MTCT. METHODS: The NISDI Perinatal and LILAC cohorts enrolled HIV-infected pregnant women and their infants in Latin America and the Caribbean. This substudy evaluated the HCV infection status of mothers at participating sites and their live born, singleton infants who had a 6-month postnatal visit by December 31, 2008. Mothers who were anti-HCV-positive, or who had CD4 counts (cells/mm(3)) <200 with detectable HCV RNA, were considered HCV-infected. All HCV-infected women were tested for HCV RNA. Infants with HCV RNA were considered HCV-infected. RESULTS: Of 1042 enrolled women, 739 (71%) mother-infant pairs met the inclusion criteria. Of the 739 women, 67 (9%) were anti-HCV-positive and 672 anti-HCV-negative [68 (10%) with CD4 counts <200; of these, 3 (4.4%) were HCV RNA-positive]. Therefore, our study population comprised 70 HCV-infected (47 with HCV RNA) and 669 HCV-uninfected women (and their infants). Factors associated with maternal HCV infection included unemployment (odds ratio [OR] = 2.58); tobacco (OR = 1.73) or marijuana (OR = 3.88) use during pregnancy; enrollment HIV viral load ([VL] copies/mL) ≥10 000 (OR = 2.27); HIV clinical disease stage C (OR = 2.12); and abnormal alanine aminotransferase (OR = 4.24) or aspartate aminotransferase (OR = 11.98). Four of 47 infants (8.5%) born to HCV-viremic women were HCV-infected, and all 4 mothers had HIV VL <1000 at hospital discharge after delivery. CONCLUSIONS: HCV MTCT among HIV/HCV-coinfected women with well-controlled HIV disease may be lower than reported in other coinfected populations. Studies with longer infant follow-up are needed.